Synthesis, Characterization and spectroscopic study of new NNS Schiff base and its Cu(II), Cd (II) and Zn(II) metal complexes (Journal of the College of Basic Education, 2023)
Novel copper(II), cadmium(II) and zinc(II) complexes of general formula, [M(NNS)2] (NNS = uninegatively charged tridentate ligands formed by condensation of 6-methyl pyridine-2-carbaldehyde with 2-methylbenzyl hydrazinecarbodithioate) have been synthesized and characterized using different physico-chemical techniques. The complexes have tetrahedral geometry for Zn(II) and Cd(II) complexes while Cu(II) expected to has square planner structure with the ligands coordinated to the metal ions as uninegatively charged tridentate chelating agents via the pyridine nitrogen, the azomethine nitrogen and the mercaptide sulphur atoms. The new compounds expected to shows bioactivity against bacteria, fungi and against cancer cells.